2018
DOI: 10.1515/freq-2017-0176
|View full text |Cite
|
Sign up to set email alerts
|

Design of Dual Band Dual Sense Circularly Polarized Wide Slot Antenna with C-shaped Radiator for Wireless Applications

Abstract: A low profile wide slot antenna for dual band and dual sense circular polarization (CP) is proposed here and is simulated by using HFSS simulation software.The proposed antenna having a C shaped patch for dual band operation and a wide square slot etched on the ground with two strips for CP operation. In between radiating patch and ground plane, designed antenna has a layer of easily available dielectric (FR-4) material. Proposed antenna shows an impedance bandwidth of 13.8 % at 2.38 GHz of centre frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…New asymmetric-circular shaped slotted microstrip antennas using single feed with slits for CP and RFID applications are proposed in [15], for achieving CP radiation and reduction in antenna size, the asymmetric-circular shaped slots are embedded symmetrically along the diagonal axis of a square patch. Some circularly polarized slot antennas using coplanar waveguide feed and microstrip line feed have been discussed [1619]. A novel design circularly polarized slot antenna for wideband is proposed in [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New asymmetric-circular shaped slotted microstrip antennas using single feed with slits for CP and RFID applications are proposed in [15], for achieving CP radiation and reduction in antenna size, the asymmetric-circular shaped slots are embedded symmetrically along the diagonal axis of a square patch. Some circularly polarized slot antennas using coplanar waveguide feed and microstrip line feed have been discussed [1619]. A novel design circularly polarized slot antenna for wideband is proposed in [16].…”
Section: Introductionmentioning
confidence: 99%
“…The CP radiation of the presented antenna [17] is obtained by using a modified square ring slot in the ground plane. A low profile, dual band, dual sense circularly polarized wide slot antenna is proposed in [19]. The dual band and CP radiation of the designed antenna [19] are obtained by C shaped patch and wide square slot etched on the ground plane with two strips.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], a dual-band dual-sense CP generated by etching asymmetrical T slot in the center of the radiator patch as well as truncated triangle strips from opposite corners and a pair of the vertical slot. In [14], a C-shaped radiator printed on the substrate and excited by direct feedline while wide slot with two asymmetrical strips in the opposite direction on the other side used for achieving dual band dual-sense CP. In [15], a tilted D-shaped radiator fed by a microstrip feed line with a suitable impedance transformer and a reduced ground plane on the other side has been configured to perform dualband dual-sense CP.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several methods have been adopted by various researchers for designing CP antennas, with some of them involving truncation, cutting of slots, slits on patch, and various other methods. [2][3][4][5][6] The above-mentioned techniques led to CP waves being radiated by the antenna but the presence of surface waves led to degradation of its performance in terms of gain and efficiency. To avoid the degradation of the performance due to surface waves, researchers introduced electromagnetic bandgap structures (EBG), which, by introducing a specified stop band/ pass band, prevent/assist surface waves from propagating, and thus improve the antenna's performance.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that due to their structural simplicity, compactness, and affordability, the single feed CP antennas were preferred in comparison to their dual feed counterparts . Several methods have been adopted by various researchers for designing CP antennas, with some of them involving truncation, cutting of slots, slits on patch, and various other methods . The above‐mentioned techniques led to CP waves being radiated by the antenna but the presence of surface waves led to degradation of its performance in terms of gain and efficiency.…”
Section: Introductionmentioning
confidence: 99%